RESPON TINGKAT KEPADATAN TELUR IKAN GURAMI (Osphronemus gouramy. Lac. ) YANG BERBEDA TERHADAP DAYA TETAS TELUR. - Muhammad Sugihartono (Jurnal Ilmiah Universitas Batanghari Jambi, 2013)
Carp ( Osphronemus gouramy . LAC . ) Is one type of fish consumption with high economic value , the constraints faced by the farmers , to address the availability of fish seed this , it would require an effort in producing large quantities of seed . Starting from these two , required a study of the density of seed in a hatchery media , in order to know how big an influence on the response of the density of egg hatchability of carp eggs . This study uses Aquarium size 50 x 60 x 30 cm 16 units , respectively - each aquarium filled with different carp eggs is A. 4 eggs / liter of water , B. 8 eggs / liter of water , C. 12 grains / liter of water , and D. 16 eggs / liter water tank with water level at 20 cm . The design used was CRD ( completely randomized design ) . Results of research conducted is obtained as follows ; densities of carp eggs in a medium will significantly affect hatchability and mortality of eggs and larvae of carp , which is a good density on treatment A ( 4 points / liter of water ) followed by treatment B ( 8 points / liter of water ) and treatment C ( 12 grains / liter ) and the last one is in treatment D ( 16 grains / liter ) in the treatment D where there are many eggs are dead / not hatch . Thus untu carp hatcheries should use a density of 4 eggs / liter of water .Keyword :  density, carp eggs, egg hatchability.